Advances in Mineral Nutrition Transport and Signal Transduction in Rosaceae Fruit Quality and Postharvest Storage - Bai, Qian; Shen, Yuanyue; Huang, Yun (Frontiers in Plant Science, 2021)
Mineral nutrition, taken up from the soil or foliar sprayed, plays fundamental roles in plant growth and development. Among of at least 14 mineral elements, the macronutrients nitrogen (N), potassium (K), phosphorus (P), and calcium (Ca) and the micronutrient iron (Fe) are essential to Rosaceae fruit yield and quality. Deficiencies in minerals strongly affect metabolism with subsequent impacts on the growth and development of fruit trees. This ultimately affects the yield, nutritional value, and quality of fruit. Especially, the main reason of the postharvest storage loss caused by physiological disorders is the improper proportion of mineral nutrient elements. In recent years, many important mineral transport proteins and their regulatory components are increasingly revealed, which make drastic progress in understanding the molecular mechanisms for mineral nutrition (N, P, K, Ca, and Fe) in various aspects including plant growth, fruit development, quality, nutrition, and postharvest storage. Importantly, many studies have found that mineral nutrition, such as N, P, and Fe, not only affects fruit quality directly but also influences the absorption and the content of other nutrient elements. In this review, we provide insights of the mineral nutrients into their function, transport, signal transduction associated with Rosaceae fruit quality, and postharvest storage at physiological and molecular levels. These studies will contribute to provide theoretical basis to improve fertilizer efficient utilization and fruit industry sustainable development.